Immobility of isolated swarmer cells due to local liquid depletion - Ajesh Jose; Benjamín Pérez-Estay; Shira Omer Bendori; Avigdor Eldar; Daniel B. Kearns; Gil Ariel; Avraham Be’er (Communications Physics)
Abstract Bacterial swarming is a complex phenomenon in which thousands of self-propelled rod-shaped cells move coherently on surfaces, providing a highly studied example of active matter. However, bacterial swarming is different from most studied examples of active systems because single isolated cells do not move, while clusters do. The biophysical aspects underlying this behavior are unclear. In this work we explore the case of low local cell densities, where single cells become temporarily immobile. We show that immobility is related to local depletion of liquid. In addition, it is also associated with the state of the flagella. Specifically, the flagellar bundles at (temporarily) liquid-depleted regions are completely spread-out. Our results suggest that dry models of self-propelled agents, which only consider steric alignments and neglect hydrodynamic and hydration effects, are oversimplified and are not sufficient to describe swarming bacteria.